Upaya Meningkatkan Minat Baca Siswa Sekolah Dasar Melalui Media Pembelajaran Berbasis E-Bookstory - Alifia Bilqish; Erina Damayanti; Irma Sari Harahap; Nurul Sakinah; Rabiatul Adawiyah Batubara (Jurnal Riset Rumpun Ilmu Bahasa, 2023)
Reading is the pronunciation of words and the acquisition of words from printed materials. In the era of education 4.0, students' interest in reading, especially students at the elementary school level, needs to be improved. The era of education 4.0 is a challenge in itself, including for elementary schools in fortifying students from the negative impact of the rapid use of technology, especially in students' daily lives. Based on these conditions, the author is interested in discussing a media called E-bookstory to improve students' reading literacy. This research uses the library research method, which is research whose object of study uses library data in the form of books or journals as its data source. Digital books, also known as e-books, are publications consisting of text, images, video or sound, published in digital form and can be read on a computer or other electronic device. One of the efforts that can be made by educational personnel is to use E-Bookstory media. Interest in reading will arise among children when they find interesting books and contain important knowledge in books, with that children become trained and diligent when reading.